190PDetails of response with first-line gemcitabine and nab-paclitaxel therapy in patients with advanced pancreatic cancer. (24th November 2019) - Nagata, Y; Kinoshita, C; Ishimoto, U; Kano, T; Ishikawa, M; Mikuni, H; Nakatsuka, K; Harada, K; Nishimura, T; Noguchi, M; Sawada, R; Amano, K; et al.
Abstract: Background: The combination of gemcitabine and nab-paclitaxel (GnP) has been established as the first-line chemotherapy in patients (pts) with metastatic pancreatic cancer (M-PC). However, the efficacy of the therapy in pts with borderline resectable PC (BR-PC) and locally advanced PC (LA-PC) is not clear. Although achieving R0 resection is one of the main target for these pts, the details of the response, such as the best time to evaluate the response is not clear. Therefore, we evaluated the details of response with GnP treatment. Methods: We retrospectively reviewed the medical records of pts with BR-PC, LA-PC, and M-PC who received GnP as the first-line chemotherapy between January 2016 and April 2019 at six hospitals. We investigated time to response (TTR), duration of response (DoR), and depth of response (DpR). The response of the primary tumor and the metastases were evaluated separately in pts with M-PC. The response of the primary tumor was evaluated in all pts. Results: A total of 47 pts were analyzed; the median age was 70 years, male was 66% and the number of pts with BR-PC/LA-PC/M-PC was 6%/26%/68%. The response rates of primary tumor and metastases were 40% and 31%, respectively. Among the pts with M-PC, seven had a partial response (PR) of the primary tumor without PR of metastases. The median TTR and time to best response of the primary tumor and metastases were 3.17 months (m) and 4.21 m (p = 0.191), and 4.11 m and 5.88 m (p = 0.724), respectively. The median DoR of the primary tumor and metastases were 5.36 m and 4.11 m, respectively (p = 0.277). The median DpR of the primary tumor and metastases were 28.3% and 15.3%, respectively (p = 0.733). The median progression-free survival and overall survival in M-PC pts with and without PR of the primary tumor were 8.48 m and 6.41 m (p = 0.267), and 14.72 m and 7.66 m (p = 0.186), respectively. Conclusions: The response of the primary tumor tended to be higher and earlier than that of the metastases. A favorable efficacy was observed in pts with BR-PC and LA-PC as well as pts with M-PC. This study indicated that the best time to evaluate the response of the primary site to consider the conversion therapy was around 4 m. Pts with M-PC showing PR of the primary tumor tended to have a favorable prognosis. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.